Emotional profiles regarding maths among primary school children – A two-year longitudinal study. - Mata, Lourdes (2021)
. . . Learning maths is challenging for many primary school students, and teachers must understand students’ learning and emotional processes specific to learning maths. The current research, grounded in control-value theory, focused on achievement emotions regarding maths. Primary school students (N = 71) were studied with the primary objective of examining the longitudinal trajectories of achievement emotions of third graders over two years. The Portuguese Achievement Emotions Questionnaire for Elementary Students was administered biannually to assess enjoyment, anxiety, and boredom regarding maths. The results indicate that enjoyment decreased and boredom increased over time, revealing three emotional profiles: positive, negative and moderate. The positive profile showed the highest scores in maths achievement. Profile membership was moderately stable and became increasingly stable and structured. In examining the complexity of students’ emotional profiles and processes, the importance of understanding them to enhance educational support, development, and learning was highlighted. .